3D printing in zoological systematics: Integrative taxonomy of Labrys chinensis gen. nov., sp. nov. (Nematoda: Tylenchomorpha). (12th October 2017) - Qing, Xue; Bert, Wim
Abstract: Three‐dimensional printing technology has shown its importance in many fields. In this study, the potential of this technique in zoological systematics was assessed. For the first time, 3D printed models were incorporated in the description of a new genus as a complement to pictures and drawings to illustrate complex 3D structures and to be used in education. Hereby, we also tested the performances of different printing materials and suggest resin as the most suitable option for the zoological field. As a case study, Labrys chinensis gen. nov., sp. nov. was described using an integrative approach: detailed morphology based on light‐ and electron microscopy, phylogenetic position as revealed from two ribosomal RNA genes, generic traits were tested for homoplasy, and the intra‐ and interpopulation variations of four sampled populations were analyzed. The new genus belongs to the subfamily Tylenchinae, family Tylenchidae in the infraorder Tylenchomorpha. It is characterized by a unique labial plate that has four narrow lobes with tips detached from the adjacent cuticle, laterally broad elongated amphidial apertures, a strong sclerotized excretory duct, a round spacious postvulval uterine sac, and a spicule with a sharp protrusion at the blade. Abstract : A new nematode genus was described using integrative approach: Morphology, molecular phylogeny, and the intra‐ and inter‐population variations of four sampled populations were analyzed. Three‐dimensional printed models were incorporated in the description of a new nematode genus as a complement to pictures and drawings to illustrate complex 3D structures and to be used in education. Hereby, we also tested the performances of different printing materials and suggest resin as the most suitable option for the zoological field.